Do suicide characteristics differ by age in older people?. (13th July 2017) - Cheung, Gary; Merry, Sally; Sundram, Frederick
ABSTRACT: Background: Suicide rates increase with age in the population aged over 65 years. The aims of this study were to (i) report the characteristics of older people who died by suicide; and (ii) investigate whether these characteristics differ in three age bands: 65–74 years, 75–84 years, and 85+ years. Methods: Using information from national coroner records, relevant socio-demographic and clinical factors in all suicides (age ≥ 65 years; n = 225) from July 2007 to December 2012 in New Zealand were analyzed and compared in the three age bands. Results: We found the older the person, the more likely they are to be widowed but the less likely to have a past psychiatric admission or recent contact with psychiatric services in the month prior to suicide. However, most of the older people (61.7% of 65–74 years, 65.6% of 75–84 years, and 77.3% of 85+ years) had contact with their general practitioner within one month of suicide. Women were less likely to use violent methods than men in all three age bands but with increasing age, men were less likely to use violent methods. Conclusions: Suicide characteristics in older people differ by age. The oldest people who die by suicide are not necessarily under psychiatric services and may benefit from a primary care-based approach in which there is screening for depression and suicide risk.